2021
DOI: 10.3389/fonc.2021.679334
|View full text |Cite
|
Sign up to set email alerts
|

Downregulated ARID1A by miR-185 Is Associated With Poor Prognosis and Adverse Outcomes in Colon Adenocarcinoma

Abstract: AT-rich interaction domain 1A (ARID1A) is a tumor suppressor gene that mutates in several cancer types, including breast cancer, ovarian cancer, and colorectal cancer (CRC). In colon adenocarcinoma (COAD), the low expression of ARID1A was reported but the molecular reason is unclear. We noticed that ARID1A low expression was associated with increased levels of miR-185 in the COAD. Therefore, this study aims to explore ncRNA-dependent mechanism that regulates ARID1A expression in COAD regarding miR-185. The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…As aforementioned, there are several previous studies demonstrating the association between ARID1A down-regulation and CRC in human tissues or animal models 16 - 22 . Herein, we thus focused our attention on the cellular mechanism study, whereas a validation to demonstrate the down-regulation of ARID1A expression in CRC tissues was not done.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…As aforementioned, there are several previous studies demonstrating the association between ARID1A down-regulation and CRC in human tissues or animal models 16 - 22 . Herein, we thus focused our attention on the cellular mechanism study, whereas a validation to demonstrate the down-regulation of ARID1A expression in CRC tissues was not done.…”
Section: Discussionmentioning
confidence: 84%
“…In concordance, a more recent study has shown that 12/18 (approximately 67%) of CRC tissues had no or low ARID1A expression 17 . Additionally, several previous studies using human specimens or animal models have reported an association between ARID1A down-regulation and CRC tumorigenicity 18 - 22 . Moreover, the loss of ARID1A is associated with the poorly differentiated grade of CRC cells 16 .…”
Section: Introductionmentioning
confidence: 95%
“…Intriguingly, in six cases ARID1A was lost at IHC, even if no alterations were detectable in the ARID1A sequence. In these samples it is possible that a loss of protein immunostaining is due to epigenetic mechanisms [34,35], including, but not limited to, ARID1A copy-number aberration [36], or the microRNAs effect [37]. In five cases a mutation in the ARID1A sequence did not correspond to a loss of protein expression.…”
Section: Discussionmentioning
confidence: 98%
“…AT-Rich Interactive Domain-containing protein 1A (ARID1A), as one of the components making up the largest SWI/SNF subunit together with AT-Rich Interactive Domain-containing protein 1B (ARID1B), is the most frequent target of SWI/SNF mutations. mutations in ARID1A impair enhancer-mediated gene regulation and prognosis in patients with colon cancer ( 124 , 125 ). Interestingly, SWI/SNF complex stability is also vital for tumor cell viability, which might be impaired by ARID1A mutation.…”
Section: Mechanisms Of Immunotherapy Resistancementioning
confidence: 99%